Career Development Program, Commitment and Communication on Employee Productivity in Nepalese Commercial Banks - Chhetri, Guna Raj; Poudel, Pawan (Journal of Balkumari College, 2024)
The major objective of the study is to analyze the effect of career development program, commitment and communication on employee’s productivity in Nepalese commercial banks. This study uses questionnaires survey method using multiple choice, ranking scale. Likert scale and other demographic information were used to collect primary data. The Likert scale on different variables like career development, commitment, communication, training, reward and work environment measured in 5-point Likert scale and weighted mean value of each variable were used to examine the relationship between dependent and independent variables as for the study purpose. This study showed career development, commitment, communication, training, reward and work environment have positive impact on employee productivity in Nepalese commercial banks. This indicates that better career development program, commitment, communication, training, reward and work environment leads to increase employee productivity in Nepalese commercial banks. The study also concludes that training followed by reward and work environment is the most influencing factor that explains employee productivity in Nepalese commercial banks.